2001
DOI: 10.1046/j.1365-2249.2001.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rheumatoid synoviocyte proliferation by endogenous p53 induction

Abstract: SUMMARYThe p53 tumour suppressor protein protects cells from tumorigenic alterations by inducing either cell growth arrest or apoptosis. In the present study, we investigated the role of endogenous p53 expressed in rheumatoid arthritis synovial fibroblasts which show transformed-appearing phenotypes. Type B synovial cells (fibroblast-like synovial cells) were exposed to a proteasome inhibitor, carbobenzoxylleucinyl-leucinyl-leucinal (MG-132). During this process, the expressions of p53 and p21 were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…However, transduction of RA FLS with p53, followed by an elevation of p21 expression, failed to trigger RA FLS apoptosis [53], suggesting that in these cells p53 pathway is more critical for the cell cycle regulation. Consistently, data from in vitro studies indicate that it is possible to inhibit RA FLS proliferation by manipulation of the expression of either p53 or p53-dependent cell cycle regulators, e. g.: using proteasome inhibitor that results in accumulation of endogenous p53 and up-regulation of p21 CDKI [54], by transfer of p21 gene into the cells [51,54], or treatment with PCNA anti-sense oligodeoxynucleotides [19]. Importantly, present studies revealed that inhibition of RA FLS proliferation can easily be achieved by treatment of the cells with Tau-Cl that modifi es expression of all above proteins.…”
Section: Discussionmentioning
confidence: 64%
“…However, transduction of RA FLS with p53, followed by an elevation of p21 expression, failed to trigger RA FLS apoptosis [53], suggesting that in these cells p53 pathway is more critical for the cell cycle regulation. Consistently, data from in vitro studies indicate that it is possible to inhibit RA FLS proliferation by manipulation of the expression of either p53 or p53-dependent cell cycle regulators, e. g.: using proteasome inhibitor that results in accumulation of endogenous p53 and up-regulation of p21 CDKI [54], by transfer of p21 gene into the cells [51,54], or treatment with PCNA anti-sense oligodeoxynucleotides [19]. Importantly, present studies revealed that inhibition of RA FLS proliferation can easily be achieved by treatment of the cells with Tau-Cl that modifi es expression of all above proteins.…”
Section: Discussionmentioning
confidence: 64%
“…Primary synovial cell lines were established as previously described (16). Synovial tissue was minced into small pieces (ϳ1 mm 3 ) in prewarmed Dulbecco's modified Eagle's medium (DMEM; Gibco Invitrogen, Carlsbad, CA). The small pieces of synovial tissue were incubated for 2 hours at 37°C in the presence of 1 mg/ml of type I collagenase (Sigma, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…After incubation at 37 • C for an additional 6 h, the cells were centrifuged at 1000 × g for 10 min and all the supernatants were aspirated without disturbing the pellet. The formazan crystals were dissolved by the addition of 120 l dimethylsulfoxide (DMSO) and oscillated for 30 s (Migita et al, 2001). The absorbance (A) was measured at 490 nm and the results were expressed as mean of triplicate wells.…”
Section: Fls Proliferation Assaymentioning
confidence: 99%